A heavy metal-free CuInS2 quantum dot sensitized NiO photocathode with a Re molecular catalyst for photoelectrochemical CO2 reduction - Huang,J; Xu,B; Tian,L; Pati,PB; Etman,AS; Sun,J; Hammarström,L; Tian,H (Chemical Communications, 2019)
Heavy metal-free CuInS2 QDs as a photosensitizer and a Re molecular catalyst have been successfully employed to co-sensitize a NiO photocathode for CO2 reduction into CO.